The effects of service quality and memorable tourism experience toward revisit intentions: Investigating the mediating role of tourist satisfaction - Nova Eviana (Tourism)
Revisit intentions play a pivotal role in the tourist market, predicting both tourist revisits and the financial sustainability of tourism enterprises while also influencing effective destination management. This study aims to examine the impact of service quality (SQ) and memorable tourism experiences (MTE) on revisit intentions (RI), with tourist satisfaction (TS) as the mediator. Using quantitative research methods, including cross-sectional surveys through a questionnaire, this investigation has focused on the Old Town of Jakarta – a significant historical landmark – with 204 tourists participating as respondents. Through PLS-SEM analysis of the data, the findings highlight that only MTE and TS directly and significantly impact RI, with TS emerging as the most influential predictor. Furthermore, SQ positively contributes to both MTE and TS, with MTE serving as a determinant of TS. Indirectly, SQ and MTE influence RI mediated by TS. Therefore, enhancing SQ in managing the Old Town of Jakarta is crucial to providing a memorable and satisfying travel experience, thereby fostering positive future behavioral intentions.